2018
DOI: 10.1111/jog.13797
|View full text |Cite
|
Sign up to set email alerts
|

How can methods of placental delivery in cesarean section affect perioperative blood loss? A randomized controlled trial of controlled cord traction versus manual removal of placenta

Abstract: Of the studied placental delivery techniques, there were no clinically significant differences in terms of the considered intraoperative and postoperative outcomes; hence, the practice of placental delivery can be left up to obstetrician's discretion and intraoperative scenario.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 26 publications
(38 reference statements)
0
4
0
Order By: Relevance
“…These results were similar to that obtained by Ramadani (14) in which he reported that there was no significant difference in the rate of blood transfusion six patients in spontaneous separation group and five patients in manual removal group received blood transfusions. Different results were reported by Altraigey et al (20) in which they reported that there was a statistically significant higher need for using extra ecbolics among the group of spontaneous separation of placenta.…”
Section: Discussionmentioning
confidence: 57%
“…These results were similar to that obtained by Ramadani (14) in which he reported that there was no significant difference in the rate of blood transfusion six patients in spontaneous separation group and five patients in manual removal group received blood transfusions. Different results were reported by Altraigey et al (20) in which they reported that there was a statistically significant higher need for using extra ecbolics among the group of spontaneous separation of placenta.…”
Section: Discussionmentioning
confidence: 57%
“…Nurses at the forefront of patient care during childbirth possess a crucial understanding of AMTSL. They are wellversed in administering uterotonic agents, such as oxytocin or misoprostol, which stimulate uterine contractions, thereby aiding in the prompt separation and expulsion of the placenta (Altraigey et al, 2019). Nurses are skilled in monitoring the mother's vital signs and uterine contractions to gauge the effectiveness of these medications and ensure the prevention of excessive bleeding (Ramesh et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“… 3 But the ideal method of placental removal during CS is still a controversial issue. 15 The choice mainly bases on the surgeon’s preference. At present, the research of placenta resection technology mainly focus on “manual” or “spontaneous” removal.…”
Section: Introductionmentioning
confidence: 99%
“… 14 , 16 Manual placental removal remains a conflicting issue owing to the risk of postpartum hemorrhage, postpartum endometritis, and placental abnormalities in subsequent pregnancies. 13 , 15 , 17 …”
Section: Introductionmentioning
confidence: 99%